Profil Pemecahan Masalah Bentuk Aljabar Siswa Ditinjau dari Gaya Belajar - Lupna, Lupna; Nurhayadi, Nurhayadi; Idris, Mustamin; Rizal, Muh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe the profile of algebraic problem solving of grade VII students of SMP Negeri 2 Sigi in terms of learning style. The method used in this study is qualitative research. The results of this study describe the profile of algebraic problem solving of grade VII students of SMP Negeri 2 Sigi based on learning style. Subjects with a structured learning style (SV) explain information in depth and in an organized manner, plan problem solving by changing verbal sentences into mathematical sentences, and re-check their reasons carefully. Subjects with a more open learning style (SA) explain information longer, plan and solve problems in a similar way, but do not check their explanations, resulting in errors. Meanwhile, subjects with a less structured learning style (SK) write information in a less organized manner, but still plan and solve problems with the right steps, and re-check the results. Overall, this study shows that learning style influences the way students understand, plan, and re-check algebraic problem solving. Keywords: Algebraic Form, Learning Style, Problem Solving.